At the dawn of history: the late pre-Islamic age in South-Eastern Arabia - Yule, Paul; Mauro, Fausto (The archaeological heritage of Oman, 2025)
This study re-evaluates the Samad Late Iron Age (SLIA) and its context around 0 CE, highlighting its complexities and significance. It examines SLIA's relationship with Mleiha/PIR, covering burial practices, pottery, trade, and architecture, offering insights into pre-Islamic south-eastern Arabia and contributing to archaeological discourse.